Marksowski materializm historyczny – koncepcja związku między bazą a nadbudową oraz prymatu czynników ekonomicznych - Cichoracki, Michał (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
Historical materialism is theoretical concept of Marxist view of history. It is described by K. Marx and F. Engels as a scientific, empirical hypothesis seeking economical factors, the changes in the modes of production and exchange as the ultimate cause, and the great moving power of all important historic events in the social and political development of society. According to this point of view changes in the productive forces of society (economical base) lead to the specific forms of social and political organization (social and political superstructure) and create some specific forms of social consciousness.